“Our Community Needs More Information About Oral Health”: Co‐Designing a Culturally Grounded Oral Health Promotion Training With Aboriginal Health Workers and Practitioners - Madison Cachagee; Ashleigh Smith; Priscilla Larkins; Michael Larkin; Dandara Haag; Eleanor Parker; Emily Minh‐An Bui; Lisa Jamieson; Brianna Poirier (Community Dentistry and Oral Epidemiology, 2026)
ABSTRACT Objectives Oral health is central to holistic wellbeing for Aboriginal and Torres Strait Islander Peoples, yet mainstream promotion approaches often rely on individualistic models that fail to reflect Community realities. Aboriginal Health Workers and Practitioners (AHW/Ps), as trusted Community members and the only nationally registered culturally based health profession, are uniquely positioned to embed oral health within relational models of care. Despite this strength, oral health remains absent from mandatory AHW/P training and continuing professional development. This paper aims to document the co‐design of a culturally grounded oral health promotion training with AHW/Ps across Aboriginal Community Controlled Health Organisations (ACCHOs) in South Australia. Methods Guided by Indigenous research methodologies, Critical Race Theory and principles of relationality, this project partnered with three ACCHOs in South Australia. The process was governed by an Aboriginal‐led Project Governance Committee (PGC) and centred on Yarning sessions, annotated worksheets and iterative feedback loops with AHW/Ps, clinic staff and Community leaders. Results A total of 34 staff across the three ACCHOs, including AHW/Ps and other clinic team members, contributed to the co‐design. Participants prioritised oral health topics relevant to everyday practice. These insights shaped a training package comprising knowledge and practical components, supported by culturally relevant visuals, character‐based videos and site‐specific referral pathways. Conclusion The co‐design process itself was a key outcome, strengthening relationships, trust and Community leadership. Effective oral health promotion must move beyond extractive models toward approaches grounded in Indigenous knowledge, reciprocity and structural change. By centring AHW/Ps, the training supports Community‐led health promotion and Aboriginal and Torres Strait Islander self‐determination in oral health.